Early States and Power in the Baltic Sea Region (8th–11th Centuries): A Comparative Study - Rizun, Nazar (European Scientific Journal, ESJ, 2021)
The aim of the article is to trace the emergence and the development of the early states of the Scandinavians, the Polabian and the Pomeranian Slavs and to investigate their main power centers. The author relies on previous research, uses theoretical achievements of historical anthropology and combines them with comparative methodology to study both archaeological and written sources. This approach allows to establish distinct political typologies in the region, namely various types of chiefdoms and principalities. The paper illuminates similar and mostly simultaneous trajectories of the evolution of those polities, emphasizes the role of central places in the respective political systems and in the governing mechanisms. During the late 8th – the early 11th centuries there had existed complex chiefdoms and chiefdom confederacies, which slowly declined towards the end of the period.